2018
DOI: 10.3390/e20060477
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity Measures Associated with the Fluctuations of the Entropy in Natural Time before the Deadly México M8.2 Earthquake on 7 September 2017

Abstract: We analyse seismicity during the 6-year period 2012-2017 in the new time domain termed natural time in the Chiapas region where the M8.2 earthquake occurred, Mexico's largest earthquake in more than a century, in order to study the complexity measures associated with fluctuations of entropy as well as with entropy change under time reversal. We find that almost three months before the M8.2 earthquake, i.e., on 14 June 2017, the complexity measure associated with the fluctuations of entropy change under time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…Furthermore, we plan to study β min as precursors to strong avalanches observed in EQ models which can produce a large amount of data such as the Carlson-Langer model [109] or the Olami-Feder-Christensen model [110] to see if they show a similar drop in the variability. Concerning the latter model, it has been studied by means of the entropy in natural time [17] revealing minima of the entropy change ∆S under time reversal which have been also observed before strong EQs [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we plan to study β min as precursors to strong avalanches observed in EQ models which can produce a large amount of data such as the Carlson-Langer model [109] or the Olami-Feder-Christensen model [110] to see if they show a similar drop in the variability. Concerning the latter model, it has been studied by means of the entropy in natural time [17] revealing minima of the entropy change ∆S under time reversal which have been also observed before strong EQs [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…NTA has found applications in a wide variety of fields ranging from cardiology (see, e.g., [12][13][14][15]) to statistical physics (see, e.g., [16][17][18][19][20][21]), and atmospheric science (see, e.g., [22][23][24]). One of the main applications of NTA, however, is the study of the physics of EQs (see, e.g., [25][26][27][28][29][30][31][32][33][34][35][36][37]). In addition, natural time is considered as the basis of the "nowcasting earthquakes" methodology that has been introduced recently [38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…For example, S has been applied for the identification of the time of an impending sudden cardiac death risk (Varotsos et al, 2007). Furthermore, it has been used for the study of the predictability of the Olami-Feder-Christensen (OFC) model for earthquakes (Olami et al, 1992), which is probably (Ramos et al, 2006) the most studied nonconservative self-organized criticality (SOC) model. The OFC model originated by a simplification of the Burridge and Knopoff spring-block model (Burridge and Knopoff, 1967) by mapping it into a non-conservative cellular automaton simulating the earthquake's behavior and introducing dissipation in the family of SOC systems.…”
Section: Natural Time Analysis Backgroundmentioning
confidence: 99%
“…In particular, it was found that exhibits a clear minimum [ 11 ] (or maximum if we define [ 15 ] instead of used here, see Section 2 ) before a large avalanche in the OFC model, which corresponds to a large earthquake. Furthermore, in a more recent study [ 18 ], by analyzing the seismicity during the six-year period 2012–2017 in natural time in the Chiapas region where the M8.2 earthquake occurred, we found that, on the same date as above, i.e., 14 June 2017, the complexity measure (see Section 2 ) associated with the fluctuations of the entropy change under time reversal exhibits an abrupt increase along with a simultaneous increase of the Tsallis entropic index q [ 19 , 20 , 21 , 22 , 23 , 24 ].The temporal variations of the latter entropic index before strong earthquakes arouse an intense international interest and has been studied by several workers [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%